Impact of climate change, variability and adaptation strategies on agriculture in semi-arid region - Aminu Saad Said, 1996-, author 620657 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Sarjana Kejuruteraan(Hydraulik dan Hydrologi))